Marketing Distribution Strategy for Beef Cattle Through the Sea Toll Road in North Gorontalo Regency - Muhammad Ashar; Mahludin Baruwadi; La Ode Sahara; Ria Indriani; Sri Yenny Pateda (International journal of technology and education research, 2026)
This study aims to analyze strategic environmental factors and formulate a marketing distribution strategy for beef cattle through the Sea Toll Road in North Gorontalo Regency. The research method used is a survey method. Primary data were collected through interviews and questionnaires to respondents from technical agencies, academics, professional associations, and beef cattle marketing distribution business actors. Secondary data were obtained from agencies related to beef cattle marketing distribution. Data were processed and analyzed using a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The results show that the role of the Sea Toll Road as a marketing distribution channel is increasingly stable in meeting the demand for beef cattle in Kalimantan. Internal Factor Scores (IFAS = 3.21) and External (EFAS = 2.99) are positive, supported by the supply of beef cattle, policy support, and the homebase of the livestock transport ship KM Camara Nusantara 5. The diagram of the position of beef cattle marketing distribution through the Sea Toll Road in North Gorontalo Regency is in Quadrant I which supports an Aggressive Strategy. The optimal strategy formulation that can be implemented is an Aggressive Strategy, namely using all strengths to take advantage of all existing opportunities.